Dynamically Tunable Electromagnetically Induced Transparency in Graphene-Based Coupled Micro-ring Resonators - Xuetong Zhou; Tian Zhang; Xiang Yin; Lin Chen; Xun Li (IEEE Photonics Journal)
A dynamically tunable electromagnetically induced transparency (EIT) system consisting of two coupled micro-ring resonators, one of which is embedded with a graphene layer, is proposed and numerically demonstrated. The effective refractive index of the graphene-based micro-ring resonator can be significantly tuned by varying the gate voltage applied on graphene, inducing significant modulation of the resonant wavelength of EIT transparency window over a wide spectral bandwidth. Typical tunability of the EIT resonance is approximately 1.62 nm/V around 1550 nm, which is much better than that based on a nanoelectromechanical EIT system. Such a configuration implies the possibility of constructing various optical devices toward realization of photon pulse trapping, optical modulation, and filtering on a chip.